Damage to posterior parietal cortex impairs two forms of relational learning - Robinson, Siobhan; Bucci, David J. (Frontiers in Integrative Neuroscience, 2012)
The posterior parietal cortex (PPC) is a component of a major corticohippocampal circuit that is involved in relational learning, yet the specific contribution of PPC to hippocampal-dependent learning is unresolved. Additionally, a role for PPC in various forms of attention has also been identified. The present study sought to merge these areas of research by testing the hypothesis that PPC is critical for relational learning under conditions in which attentional demands are high. In Experiment 1, sham or electrolytic lesions of the PPC were made before rats were tested on a three-phase sensory preconditioning task. During the first phase, half of the training trials consisted of pairings of an auditory stimulus followed by a light. During the other trials, a second auditory stimulus was presented alone. In the next phase of training, the same light was paired with food, but no auditory stimuli were presented. During the final phase of the procedure both auditory stimuli were presented in the absence of reinforcement during a single test session. As is typically observed during the test session, control rats exhibited greater conditioned responding to the auditory cue that was previously paired with light compared to the unpaired cue. In contrast, PPC-lesioned rats responded equally to both auditory cues. In Experiment 2, PPC-lesioned and control rats were trained in a compound feature negative discrimination task consisting of reinforced presentations of a tone alone and non-reinforced simultaneous presentations of a light-tone compound stimulus. Control rats but not rats with damage to the PPC successfully learned the discrimination. Collectively, these results support the idea that the PPC contributes to relational learning particularly under conditions of high attentional load.